Effectiveness of Hypnobreastfeeding on Exclusive Breastfeeding at Mumbulsari Community Health Center Work Area - Ni Ny Wedarthani Achintya A; Nurul Azizah; Ega Delva; Tamina Melindah; Diah Astini Paramita (International Journal Of Health Science, 2025)
Exclusive breastfeeding is the best period of breast feeding intake for infants because it maximizes health benefits for growth and development. However in reality, there are many hindrances for mothers to give exclusive breastfeeding. Negative perceptions from the mothers itself regarding breast milk often caused the low rates of exclusive breastfeeding. Conventional therapies that has been given only solved one problem at a time, while the actual solution is a holistic care which includes mind, body, and soul. Hypnobreastfeeding is one of the preferred therapy that contains holistic care to improve the exclusive breastfeeding. The aim of this study is to analyze the effect of hypnobreastfeeding on exclusive breastfeeding at Mumbulsari Community Health Center, Jember, East Java, Indonesia. This study used pre-experimental design with post-test only design on pregnant women in third trimester. Simple random sampling was used as sampling technique with 16 treatment group and 16 control group which fulfill inclusion and exclusion criteria. The experimental data was collected using observation sheets which then statistically analyzed using bivariate chi-square test. The result of chi-square test showed that p=0,003 (p < 0,05) which shows that hypnobreastfeeding positively influence exclusive breastfeeding. In conclusion, hypnobreastfeeding is strongly suggested as the treatment to improve exclusive breastfeeding on mothers.